2022
DOI: 10.1227/neu.0000000000002287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Selective Tibial Neurotomy for the Spastic Foot Treatment Using a Personal Goal-Centered Approach: A 1-Year Cohort Study

Abstract: BACKGROUND:Selective tibial neurotomy (STN) has already demonstrated its effectiveness to reduce foot deformities and spasticity, but assessment according to a goal-centered approach is missing.OBJECTIVE:To evaluate the effectiveness of STN associated with a postoperative rehabilitation program for the treatment of the spastic foot, according to a goal-centered approach.METHODS:Interventional study (before-after STN and rehabilitation program) with observational design including consecutive adult patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…7 A recent large-scale study of 104 patients used a Goal Attainment Scale and reported that >90% achieved their primary personal goals (ie, comfort when walking) at 1 year after surgery with a third far exceeding expectations. 9 Six of these patients had complications with plantar foot numbness that resolved, which could again be attributed to the authors performing a partial neurotomy at the proximal trunk containing mixed motor/ sensory fibers. Two patients required washout for infection.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…7 A recent large-scale study of 104 patients used a Goal Attainment Scale and reported that >90% achieved their primary personal goals (ie, comfort when walking) at 1 year after surgery with a third far exceeding expectations. 9 Six of these patients had complications with plantar foot numbness that resolved, which could again be attributed to the authors performing a partial neurotomy at the proximal trunk containing mixed motor/ sensory fibers. Two patients required washout for infection.…”
Section: Resultsmentioning
confidence: 96%
“…Cases of sensory loss or pain were exclusive to cases primarily involving the toe flexors and some TP, where this was accomplished by neurotomy of the tibial trunk. Despite a single case series of 4 patients suggesting a lack of persistence in effect at 6 months, 18 subsequent reports have shown strong support to the contrary, 7-10 suggesting that a more extensive neurotomy might have been required in the former. A prospective series of 51 patients demonstrated a lasting improvement in spasticity, motor control of dorsiflexion, ankle positioning, and gait and balance at 2 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this study supports our findings of high satisfaction with these personalized goals after STN. 37 This finding demonstrates the importance of emphasizing validated gait and balance assessments, which are currently underrepresented in the literature. 13…”
Section: Discussionmentioning
confidence: 95%